A portrait of the female labor market in Tocantins between 2000 and 2021 - de Carvalho, Polliany Aparecida Lopes (Seven Editora, 2024)
The expansion of women’s participation in the labor market is a reality in Brazil, especially after the 80s. With the advent of labor rights aimed at women’s needs, such as maternity leave and special conditions and hours for breastfeeding women, and the improvement of professional qualification and educational levels; Women were able to expand their participation in the labor market. However, this higher participation is still not enough to overcome the structural disparities between the genders in the labor market. This work has as its object of analysis the state of Tocantins and as a time frame the period between 2000 and 2021, and the results show that this insertion of women still perpetuates inequalities between genders, as it occurs even in greater proportion in sectors of greater vulnerability and lower average income – commerce and services –, and also that women are concentrated in the lower average income strata, up to 3 minimum wages. DOI:https://doi.org/10.56238/sevened2024.026-059